PENERAPAN REINFORCEMENT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI - EKA MADIYA, - (2021)
Learning physical education in junior high schools with diverse materials and carried out during the pandemic is a challenge in itself. Such conditions make students' motivation in carrying out learning decreases and has an impact on learning outcomes. Therefore, it is necessary to have teacher competence in physical education learning strategies in schools, especially reinforcements to be able to motivate students. The purpose of this study was to reveal the effect of positive and negative reinforcement on learning motivation and student learning outcomes in physical education learning (PE). The method used in this research is ex post facto. The subjects in this study were 32 students in class VIII.1 and 32 students in class VIII.2. Overall, the subjects in this study were 64 students. Data collection techniques used questionnaires to measure student motivation, and report cards were used to measure student learning outcomes. The results of this study indicate that positive reinforcement has a significant effect on students' motivation and learning outcomes in physical education learning. The application of negative reinforcement also has a significant effect on learning outcomes and motivation, however, the application of negative reinforcement is the last step and is temporary. Recommendations from this research to be developed more varied in the sample and the development of other types of reinforcement. Keywords: Positive and negative reinforcement, learning motivation, learning outcome